Swarm intelligence. Volume 2, - Tan, Ying, 1964- (The Institution of Engineering and Technology, 2018)
This book discusses several swarm intelligence algorithms, such as fireworks algorithm, predator-prey optimisation, ant lion optimiser, glowworm swarm optimisation, firefly algorithm, binary moth-flame optimisation algorithm, binary whale optimisation, grey wolf optimisation, interactive chaotic evolution and inclined planes system optimisation.
Keywords: Swarm intelligence.; Computer algorithms.; Algorithms.; elektronické knihy; electronic books